2018
DOI: 10.1097/hs9.0000000000000031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling Defines Distinct Prognostic Subgroups in Childhood AML: A Report From the French ELAM02 Study Group

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 30 publications
2
57
0
Order By: Relevance
“…Further studies are needed to extend those findings and determine whether the LSC17 score has any association with other molecular aberrations. Importantly, the LSC17 score retained a strong value in AML without favorable and adverse molecular-risk factors as previously defined by our group [ 1 ] as well as in cytogenetically normal-AML which makes up respectively 50% and 25% of all pediatric AML. This is critical in routine practice since these AML categories have been shown to display heterogeneous outcome.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Further studies are needed to extend those findings and determine whether the LSC17 score has any association with other molecular aberrations. Importantly, the LSC17 score retained a strong value in AML without favorable and adverse molecular-risk factors as previously defined by our group [ 1 ] as well as in cytogenetically normal-AML which makes up respectively 50% and 25% of all pediatric AML. This is critical in routine practice since these AML categories have been shown to display heterogeneous outcome.…”
supporting
confidence: 70%
“…Major advances have been made do better define the genetic basis of AML. Underlying cytogenetic and molecular aberrations are now routinely used to inform disease classification and stratify patients into favorable, unfavorable or intermediate risk categories, the latter encompassing about a half of patients [ 1 ]. Although outcome has greatly improved over the past decade, relapse occurs in about 30% of pediatric AML and represents the major cause of mortality.…”
mentioning
confidence: 99%
“…A report from the French study group con rmed that WT1 mutations were an independent prognostic factor for pediatric AML. 22 However, a report from the Japanese study group showed that WT1 mutations were related to a poor prognosis in patients with normal cytogenetics, excluding those with FLT3/ITD and those younger than 3 years. 23 By contrast, a report from the Nordic Society of Pediatric Hematology and Oncology (NOPHO) revealed that no signi cant correlation with survival was seen for WT1 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…However, as noted above, there are significant differences in genetic alterations between adult and pediatric patients with AML. Previous larger studies suggested that current guidelines, including the ELN guidelines, are not adequate for children with AML (14,32,33), thus, there is a need for the development of a pediatric-specific guidelines for more precise stratification.…”
Section: Discussionmentioning
confidence: 99%